Adjusting the Training Process in Judo According to Physical and Functional Parameters - Giorgi Zubitashvili (Lithuanian Sports University, 2018)
Research  background  and  hypothesis.  The  specificity  of  the  technical  performance  in  judo  demands  from athletes to perform fast and powerful actions at a high level, therefore, much importance is given to the development of aerobic capacity and supporting motor system, in particular, strength of the hand-grip function. Research aim was to study the judoka's hand-grip strength and lung vital capacity indices in the aspect of age and weight categories and find out the relation between those two factors as well as the most characteristic age period of motor development. Research methods. The studies were carried out in the preparatory periods of 2009-2011 training cycles. The subjects were 2000 male judokas in 8 different weight categories. The measurements were made using a dynamometer and dry spirometer. The obtained results were statistically processed by SPSS 19, using ANOVA test. Research results. Research results showed that the judoka's hand-grip and lung vital capacity average indices increased in each higher age and weight category, but this increase was not regular. The most obvious period of motor development at which increase in results was most noticeable was 13-15 years of age. The increase in the hand-grip strength and lung vital capacity in the age and weight categories were inversely proportional, and we found a correlation between them. Discussion and conclusion. We suggest that there is a close relationship between motor system and the muscles participating in respiration. Keywords: hand grip, lung vital capacity, data dynamics, practical use.